Johann Konrad Schwartz – an Early Modern Researcher of Plagiarism - Kyselov, Roman (Sententiae, 2025)
Johann Konrad Schwartz (1676-1747), whose professional academic life is associated with the Koburg Gymnasium, authored four printed works on the phenomenon of plagiarism. His “Book on Literary Plagiarism” (1706) constitutes a significant supplement to the principal early modern treatise on the subject, Jakob Tomasius’s “Philosophical Dissertation on Literary Plagiarism” (1673). Schwartz’s work also significantly expands the list of conditions under which the unacknowledged use of another’s text would not have been considered plagiarism by early modern intellectuals. He emphasizes the role of genre and author, arguing that not all texts entail the same expectations of originality and not all authors are equally subject to accusations of plagiarism. In early modern thought, plagiarism was regarded as the theft of the fame associated with authorship. Accordingly, Schwartz insists that before one levels such an accusation, it is essential to consider whether the text in question is, in fact, something from which fame could be derived.